Crowdfunding and entrepreneurship - Ekanem, Ignatius; Ideh, Steve (London New York, NY Routledge, Taylor & Francis Group, 2024)
"This accessible text provides an insight into the growing global trend of crowdfunding as a source of entrepreneurial finance. Grounded in the academic literature, this book looks at the micro and macro issues within crowdfunding, from the entrepreneur's access to finance at the business level, to the role of government in regulating the market. It helps the reader develop a sound understanding of crowdfunding as a source of finance, the crowdfunding process and potential options when faced with start-up funding issues. A range of international case studies of successful and unsuccessful crowdfunding campaigns help readers to apply theory to world-life scenarios. Readers are also supported throughout the book with chapter objectives and summaries, key terms, discussion questions and further reading guidance. Instructor materials such as slides and test questions are available as digital supplements. Crowdfunding and Entrepreneurship will be a valuable resource for students of new venture creation and entrepreneurial finance, as well as entrepreneurs exploring crowdfunding as an option for business development"--
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Crowd funding; Entrepreneurship